Beverly Township the study of a Rural Area - McQueen, Richard D. (My University, 1958)
Geography is a scientific subject dealing with man and his physical environment. The task of the geographer is to determine what effect the physical environment has on man and how man is best able to adapt himself to his particular environment.
Man's environment is important in all of his activities. This is especially true in the case of the farmer. Geological and geomorphological forces sculpture the shape of his land, climatic and biological forces form the soil. Once man starts working the land these forces continue to influence him n various ways. How well he adapts himself and his farming methods to the physical factors helps to determine whether he will be a success or a failure. The farmer's human environment is as important as his physical one. He is dependent on other for supplies and for a market for his goods.
The agricultural region is a very significant field for the geographer to study for here he can see an in his environment without many of the technological devices of modern civilization that tend to remove or protect man from his natural setting. Thus the object of this thesis is to study rural area, Beverly Township, and determine if man has made a suitable adjustment with his environment, both physical and human.
In a study of this type we must look at the physical nature of the region before we study man's activities. In chapter one we study geomorphological history of the township that affects present landscape. We do not delve too deeply into the subject for fear of getting lost in irrelevancies.
After the physical setting has been studied it is necessary to see how man has developed and used the land in the past. The often quoted phrase "the past is the key to the present" is a sound one in regards to this type of study. Chapter two studies the historical development of the township. Again, we try to select only the facts that will give us a better understanding of present conditions.
In chapter three we look at man and his agricultural endeavors. We see if and how he has adjusted to his environment. We look at the forces her has conquered and those with which he continues to struggle.
Although Beverly Township is basically an agricultural area. we must not forget the urban function of the small centers nor should we ignore any industries that have helped to develop the township and that might complement the agricultural function of the community. Chapter four studies the non-agricultural activities.
Chapter five is the most important chapter in the study. It is in this chapter that all our findings and conclusion are gathered together and given meaning.
Title: Beverly Township the Study of a Rural Area, Author: Richard D. McQueen, Location: Thode